Post COVID glaucoma service redesign utilising electronic patient triage and community optometry clinics (Fife, Scotland 2020—2022) - Niharika Nalagatla; Shameela Parveen; Kelvin KW Cheng; Caroline Styles; Andrew Blaikie; Peter Wilson; Bhavani Karri; David J Chinn; Roshini Sanders; Glaucoma Team; Lisa Wong; Alan Ramsay; et al. (BMC Ophthalmology)
Abstract Background COVID-19 caused a huge backlog of patients in glaucoma clinics. This study describes redesign of an entire glaucoma service with electronic patient triage to three levels and utilisation of the Scottish optometry infrastructure of upskilled optometrists. Methods 2276 patients in glaucoma clinics were identified and triaged to three levels in keeping with Glauc-strat-fast guidance with local amendments. Every patient detail was entered into a bespoke glaucoma database to include demographics, clinical findings and social deprivation scores. The database generated automatic patient, GP and optometrist letters. Level one patients (482) were discharged within the Scottish general optometry service contract. Level two patients (714) were discharged to glaucoma accredited community optometry clinics. The glaucoma consultants would discuss the optometry decision making through screen share once a week. Level three patients (1080) were retained in hospital. All outcomes were audited and analysed 24 months after the new service. Results Statistically significant parameters were found between the three groups, to include more normal eyes, less mean deviation on visual fields and less social deprivation in level one patients. After 24 months level one patients had a return rate of 40.2%, mainly for other diseases with only 20.4% retained within hospital or level two. 9.4% of level two patients returned to hospital with retention of only 2.7% in hospital at 24 months. Conclusion Glaucoma patients in Scotland can be appropriately triaged to glaucoma accredited community optometry clinics. This frees capacity within hospital to see patients with moderate and severe disease in a timely fashion, for best visual outcomes.